2023
DOI: 10.20944/preprints202301.0204.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

<strong></strong>Forgotten “Primum Non Nocere” and Increased Mortality after Covid-19 Vaccination <strong> </strong>

Abstract: Background. The main impetus behind the worldwide Covid-19 vaccination campaign in 2021 was to reduce the mortality attributed to SARS-CoV-2 infection in the preceding year. Nevertheless, rigorous analyses of the mortality benefits conferred by this massive vaccination effort have been lacking. Methods Statistics offers us an essential methodological approach for measuring the impacts of Covid-19 vaccination on public health. The mathematical relation between vaccinated-alive groups can be repeated between va… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 3 publications
(4 reference statements)
0
12
0
Order By: Relevance
“…The positive correlation of vaccination in the first month of vaccination is characteristic also for some other countries [1]. The USA is an exception in the sense that in all other countries, this positive correlation lasted only to the end of March 2021.…”
Section: The Bijective Analysis Of the Graphs Of The Intensity Of Vac...mentioning
confidence: 64%
See 3 more Smart Citations
“…The positive correlation of vaccination in the first month of vaccination is characteristic also for some other countries [1]. The USA is an exception in the sense that in all other countries, this positive correlation lasted only to the end of March 2021.…”
Section: The Bijective Analysis Of the Graphs Of The Intensity Of Vac...mentioning
confidence: 64%
“…Analysis of five-month vaccination in England has confirmed that the vaccinated part of the population has increased the mortality rate by bout 14,5% [1]. Detailed analysis for the entire years 2021 and 2022 where calculations will be done for five age groups (0-20, 21.40, 41-60, 61-80, and above 80) will give the exact increased mortality rate due to the massive Covid-19 vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several other studies have implicated COVID-19 vaccination in increased all-cause mortality. These studies have used different methods, countries, age groups, and time periods covering different COVID-19 variants, different vaccine histories, and time following vaccination [157][158][159][160][161][162][163]. A common theme is the involvement of mRNA vaccines, and poor outcomes in children and young adults.…”
Section: General Studiesmentioning
confidence: 99%